Internet connectivity disruption in Romania (Romania) - Voidly (2026)
CRITICAL severity disruption detected in Romania. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: RO-2026-0019
Keywords: internet disruption; RO; disruption; critical